2021
DOI: 10.3389/fpubh.2021.661042
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 Regulatory Response in United States-Assisted Living Communities: Lessons Learned

Abstract: Coronavirus disease 2019 (COVID-19) has disproportionately affected residents, their families, staff, and operators of congregate care settings. Assisted living (AL) is a type of long-term care setting for older adults who need supportive care but not ongoing nursing care and emphasizes a social model of care provision. Because AL is a type of long-term care, it has at times been referenced along with nursing homes in discussions related to COVID-19 but not recognized for its different care practices that pose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…However, resource constraints and organizational obstacles present significant barriers to the person-centered approach that is often required, and recommended as best practice ( 9 , 59 , 60 ). Other studies have reported similar experiences across licensed and unlicensed care staff, where organizational and systemic barriers deprioritize implementation of nonpharmaceutical interventions ( 23 , 28 , 61 , 62 ).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…However, resource constraints and organizational obstacles present significant barriers to the person-centered approach that is often required, and recommended as best practice ( 9 , 59 , 60 ). Other studies have reported similar experiences across licensed and unlicensed care staff, where organizational and systemic barriers deprioritize implementation of nonpharmaceutical interventions ( 23 , 28 , 61 , 62 ).…”
Section: Discussionmentioning
confidence: 71%
“…This study has limitations worth considering for future research efforts. Long-term care settings, including AL/RC, have been disproportionately impacted by both resident morbidity and mortality and staffing shortage burdens as a direct result of COVID-19 ( 61 , 62 ). In addition to this trauma, pandemic-related restrictions limited recruitment and data collection efforts adversely affecting our ability to build the trust and relationships necessary with frontline care staff and administrators to gain buy-in for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Together, the studies included 7379 residents and 2598 staff members, spread over 99 care homes. Two studies had no participants (staff or residents) [ 15 , 16 ] and a third study interviewed experts in the field [ 17 ]. The sample size varied widely between studies, with the regional studies of Luzón et al [ 18 ] and Vijh et al [ 14 ] having the largest numbers of participants.…”
Section: Resultsmentioning
confidence: 99%
“…Three practices were the most widespread in the framework of the operational processes: systematic polymerase chain reaction (PCR) testing of residents and professionals with symptoms of COVID as a mechanism for detecting positive cases and controlling infection [ 14 , 16 , 17 , 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 ]; the use of personal protective equipment (PPE) by facility personnel and masks by residents [ 14 , 15 , 16 , 17 , 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 ]; and restriction of outings and external visits [ 14 , 15 , 17 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Other practices commonly used included: case monitoring for the outbreak and contact tracing of COVID-19-positive individuals [ 14 , 15 , 19 , 20 , 21 , 23 , 25 , 26 , 27 ], cohort segmentation by identifying and monitoring transition zones regarding cleaning between contaminated area and other areas [ 14 , 16 , 18 ,…”
Section: Resultsmentioning
confidence: 99%
“…Caregivers in a Dutch study ( n = 1,997, April to May 2020; Wammes et al, 2020 ) reported concerns about residents’ increased loneliness (76%), sadness (66%), and decreased quality of life (62%). These high rates of caregiver concerns about resident mental health in both, AL and nursing home settings, point to the need to develop public health measures that (a) better balance residents’ mental health needs with safety concerns and (b) ensure continued inclusion of caregivers in resident care ( Dys et al, 2021 ; Hindmarch et al, 2021 ; Mitchell et al, 2021 ; Nash et al, 2021 ; Parmar et al, 2021 ; Prins et al, 2021 ; Wammes et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%